2011
DOI: 10.1128/aem.02346-10
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of an Antibiotic Downregulator Mutant and Synergistic Actinorhodin Stimulation via Disruption of a Precursor Flux Regulator in Streptomyces coelicolor

Abstract: Through microarray analysis of an antibiotic-downregulator-deleted Streptomyces coelicolor ⌬wblA ⌬SCO1712 mutant, 28 wblA-and SCO1712-dependent genes were identified and characterized. Among 14 wblAand SCO1712-independent genes, a carbon flux regulating 6-phosphofructokinase SCO5426 was additionally disrupted in the ⌬wblA ⌬SCO1712 mutant and further stimulated actinorhodin production in S. coelicolor, implying that both regulatory and precursor flux pathways could be synergistically optimized for antibiotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…3, real-time PCR analyses demonstrated that the levels of actII-orf4 transcripts were higher in the ⌬wblA mutant during the time course than in S. coelicolor M145 and the ⌬adpA mutant. It is consistent that the ⌬wblA mutant produced the highest level of actinorhodin and the ⌬adpA mutant did not produce actinorhodin at all (15,29,30). The levels of adpA transcripts from S. coelicolor M145 were similar to those in the ⌬wblA mutant, suggesting that the expression of adpA was not influenced by the wblA gene, and suggesting that the transcription of adpA occurs upstream of wblA transcription.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…3, real-time PCR analyses demonstrated that the levels of actII-orf4 transcripts were higher in the ⌬wblA mutant during the time course than in S. coelicolor M145 and the ⌬adpA mutant. It is consistent that the ⌬wblA mutant produced the highest level of actinorhodin and the ⌬adpA mutant did not produce actinorhodin at all (15,29,30). The levels of adpA transcripts from S. coelicolor M145 were similar to those in the ⌬wblA mutant, suggesting that the expression of adpA was not influenced by the wblA gene, and suggesting that the transcription of adpA occurs upstream of wblA transcription.…”
supporting
confidence: 59%
“…Based on these results, we wondered whether AdpA SC regulates wblA gene expression as an activator or repressor. To test this, transcription analysis was conducted with strains of S. coelicolor M145, the S. coelicolor ⌬wblA mutant (26,29), and the S. coelicolor ⌬adpA mutant (19). It was previously reported that the S. coelicolor ⌬wblA mutant produces a much higher level of actinorhodin than S. coelicolor M145 (29,30), whereas the adpA-deleted S. coelicolor strain does not produce actinorhodin at all in either liquid or plate cultures (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated that the effect of overexpressing zwf2 was slightly small when the three genes were overexpressed (Table S1). This might be due to the imperfect nature of the in silico metabolic model that could not account for complex regulatory mechanisms (Kim et al 2011). Besides, another reason might be the synergistic effect caused by the adjacent dptI and dptJ genes in the genome of S. roseosporus.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential targeted gene disruption of these two regulatory genes as well as SCO5426, a flux-controlling gene, resulted in a tripleknockout S. coelicolor mutant displaying significantly increased production of the polyketide antibiotic actinorhodin (15,16,46). To determine whether or not deletion of these regulatory genes could affect CsA hydroxylation activity in S. coelicolor, we introduced pMMBL312 into S. coelicolor mutants, generating S. coelicolor M145 ⌬SCO5426, S. coelicolor M145 ⌬wblA, and S. coelicolor M145 ⌬wblA ⌬SCO1712 ⌬SCO5426 (designated ESK616, ESK617, and ESK618, respectively).…”
Section: Resultsmentioning
confidence: 99%